Primary Adult Soft Tissue Sarcoma: Time-Dependent Influence of Prognostic Variables - Stojadinovic, A. (Institutional Knowledge at Singapore Management University, 2002)
PURPOSE: To define prognostic factors for postrelapse survival and their time-dependent influence for adult soft tissue sarcoma (STS). PATIENTS AND METHODS: We analyzed 2,123 patients with completely resected localized primary STS treated from 1982 to 1999. Variables studied included tumor site, size, depth, grade, and resection margin but not treatment other than resection. Landmark time frames were used to assess the influence of disease-free interval (DFI) on disease-specific survival (DSS). DSS was estimated with the Kaplan-Meier method. Univariate and multivariate analyses were performed using log-rank test and the Cox proportional hazards regression model. Time-dependent stepwise regression analysis evaluated the time-dependent influence of each variable. RESULTS: Two thirds of recurrences developed within 2 years of initial resection. Tumor size (P < .001), grade (P < .001), and microscopic resection margin (P < .001) independently predicted DSS for all STS. Size and grade independently predicted early (DFI [<=] 3 years) and margin late (DFI > 3 years) DSS. Risk of tumor-related death was the same across all sites 3 years postresection and decreased significantly for extremity/trunk STS when DFI exceeded 3 years (P < .001). Influence of initial high-risk factors for tumor-related mortality in extremity/trunk STS decreased by 40% 3 years postresection, but their influence over DSS for non-extremity/trunk sites remained constant over time. Likelihood of complete resection after recurrence (all sites) increased with DFI (9% and 33% for DFI < 6 and > 36 months, respectively). CONCLUSION: Tumor size, grade, and resection margin predict outcome for completely resected STS, and their influence for DSS is time- and site-dependent. The influence of prognostic factors changes over the natural history of extremity/trunk STS. Time to recurrence exerts significant influence over complete resection rates for recurrent disease.